"English is a mishmash of everything": Examining the language attitudes and teaching beliefs of British Asian multilingual teachers. Issue 3 (3rd July 2019) - Weekly, Robert
ABSTRACT: The author reports on a qualitative investigation of the language attitudes of multilingual British South Asian English language teachers. Data are drawn from both interviews and focus groups to demonstrate the participants underlying conception of language and their awareness and attitudes toward Indian English and how they coalesce their "duty" as English language teachers and their beliefs about language variation. The author observes underlying differences in the attitudes of first- and second-generation migrants and argues that this is related to their early experiences of English language variation and their exposure to either single- or dual-language ideologies. Therefore, the author supports other research that attitudes related to "correct" language is ingrained in childhood experiences. It is also argued that changes are required in current teacher training to raise awareness of World Englishes and English as a lingua franca to equip teachers with the necessary skills to respond to a new global linguistic landscape.